Asymmetric temporal interactions of sound‐evoked excitatory and inhibitory inputs in the mouse auditory midbrain. (16th July 2014) - Ono, Munenori; Oliver, Douglas L.
<x xml:space="preserve">Abstract</x> Key points The temporal coding of sound is critical for the auditory system. Little is known about how sound evokes the timing of synaptic currents at higher levels of the auditory system and how the integration of these currents results in neural firing. In the inferior colliculus, excitatory and inhibitory synaptic currents evoked by long‐duration sounds have different temporal properties with excitatory currents more variable than inhibitory currents. Within a neuron, the sequence of synaptic events suggests the fastest sound‐evoked excitatory postsynaptic current (EPSCs) usually followed the inhibitory postsynaptic currents (IPSCs), and the slowest EPSCs preceded by IPSCs. Knowledge about the timing of neural activity in the midbrain is important for understanding how temporally complex sounds such as speech are processed and communicated to higher centres of the system. Abstract In the auditory midbrain, synaptic mechanisms responsible for the precise temporal coding of inputs in the brainstem are absent. Instead, in the inferior colliculus (IC), the diverse temporal firing patterns must be coded by other synaptic mechanisms, about which little is known. Here, we demonstrate the temporal characteristics of sound‐evoked excitatory and inhibitory postsynaptic currents (seEPSCs and seIPSCs, respectively) in vivo in response to long‐duration tones. The seEPSCs and seIPSCs differ in the variability of their temporal properties. The seEPSCs have either early or late current peaks, and the early‐peaked currents may be either transient or sustained varieties. The seIPSCs have only early‐peaked sustained responses but often have offset responses. When measured in a single neuron, the seIPSC peaks usually follow early, transient seEPSCs, but the seIPSCs precede latest‐peaking seEPSCs. A model of the firing produced by the integration of asymmetric seEPSCs and seIPSCs showed that the temporal pattern of the early‐peaked sustained neurons was easily modified by changing the parameters of the seIPSC. These results suggest that the considerable variability in the peak time and duration of the seEPSCs shapes the overall time course of firing and often precedes or follows the less variable seIPSC. Despite this, the inhibitory currents are potent in modifying the firing patterns, and the inhibitory response to sound offset appears to be one area where the integration of excitatory and inhibitory synaptic currents is lacking. Thus, the integration of sound‐evoked activity in the IC often employs the asymmetric temporal interaction of excitatory and inhibitory synaptic currents to shape the firing pattern of the neuron.